Optimization and Sizing of a Hybrid Solar-Wind-Battery-Gasoline-Diesel System for Emission Reduction and System Stability - Diaeddeen ELmezoghi; Hmeda Musbah; Suleiman Elhamali (Surman Journal of Science and Technology, 2025)
A hybrid Solar, Wind, Battery, Gasoline and Diesel System Optimization Sizing (HSWBGDSO) model is proposed to optimize the capacity sizes of the renewable energy resources integration based on battery bank, gasoline and diesel system. The optimal renewable energy size could be reached based on the proposed constraints and the renewable energy resources availability as well as the system requirements. A cased study is discussed based on a proposed flowchart. Different scenarios of hybrid models are studied to reduce the fossil fuel emissions. Using the battery bank is playing a crucial rule for system stability due to the fluctuation of the renewables. Results show that the fossil fuel emission is reduced to 617.4 pounds which is representing 33.33 % of the original emission value.